Development status of the technology supporting system for local commoditization of fruits and vegetables in China - CAO Jinping; CHEN Yezhi; SUN Cui; WANG Yue; CHEN Kunsong; ZHANG Changfeng; SUN Chongde (浙江大学学报. 农业与生命科学版)
With the deepening of agricultural supply-side structural reform and the improvement of people’s living standards, the consumer demand and the production-marketing model of fruits and vegetables in China are undergoing tremendous changes. Accordingly, the postharvest supporting system is playing a more and more important role in the fruits and vegetables industry. After years of development, we had made great progress on the theories and technologies of postharvest fruits and vegetables. However, the local processing of fruits and vegetables were still the short board, which had become a bottleneck problem for the improvement of postharvest supporting system. Thus, the present study reviewed the development status of the technologies for local commoditization of fruits and vegetables in China, in order to provide some inspiration for the future development of this area.